Analysis of Mathematics Literacy Based on Mathematical Ability - Andes Safarandes Asmara; S. B. Waluya; Rochmad Rochmad (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2017)
This research was conducted to determine the literacy skills students of class X on their math skill. This study used a qualitative approach, the approach that drives meaningful results. To determine the ability of mathematical literacy class X, there were study subjects of 3 people who were selected based on their level of math skills. The determination was based on the categories of low, medium and high. Each subject was given a test and interview questions to determine the literacy skills. The results revealed that subjects with low category were in the second level of mathematics literacy, and subjects with high category were in the third level of mathematical literacy skills. Based on these results, it is necessary to seek strategies in the learning process of mathematics, which allows the improvement of mathematics literacy skills.